1979
DOI: 10.1007/bf01223620
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-independent diabetes: A defect in the activity of lipoprotein lipase in adipose tissue

Abstract: Summary. The activity of lipoprotein lipase (E.C.3.1.1.3.) has been measured in adipose tissue from insulin-independent diabetics with hypertriglyceridaemia, non-diabetics with hypertriglyceridaemia and control patients, all of whom were obese.Although all groups showed an increase of plasma insulin after oral glucose, both the diabetic and nondiabetic hypertriglyceridaemics had impaired activities of lipoprotein lipase in adipose tissue compared to the obese normals (p<0.02, p<0.03, respectively). A course of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
1

Year Published

1981
1981
2015
2015

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(24 citation statements)
references
References 15 publications
1
22
1
Order By: Relevance
“…Disturbances in the nutritional regulation of adipose tissue LPL activity have been observed in certain physiological and pathophysiological conditions like ageing, 11 obesity 21 and insulin resistance. 22 Bergö et al 11 reported that the downregulation of LPL activity during fasting disappeared in old rats. They suggest that loss of the ability to down-regulate the activity during fasting may result from a metabolic derangement, because old rats had elevated plasma glucose levels.…”
Section: Lpl Activity and Lipolysis During The Estrous Cyclementioning
confidence: 99%
See 1 more Smart Citation
“…Disturbances in the nutritional regulation of adipose tissue LPL activity have been observed in certain physiological and pathophysiological conditions like ageing, 11 obesity 21 and insulin resistance. 22 Bergö et al 11 reported that the downregulation of LPL activity during fasting disappeared in old rats. They suggest that loss of the ability to down-regulate the activity during fasting may result from a metabolic derangement, because old rats had elevated plasma glucose levels.…”
Section: Lpl Activity and Lipolysis During The Estrous Cyclementioning
confidence: 99%
“…24 also reported that fat cells isolated from male rats treated for 5 days with estradiol were insulin resistant. Taylor et al 22 reported that a feature in the development of insulin resistance in adult diabetics was a failure of maintenance of adipose tissue enzyme activities involved in lipid metabolism. Plasma estradiol level was highest at proestrus but LPL activity was lowest at estrus.…”
Section: Lpl Activity and Lipolysis During The Estrous Cyclementioning
confidence: 99%
“…Insulin deficiency and insulin resistance in diabetic subjects are associated with subnormal levels of LPL which are restored with insulin treatment [1,2]. In healthy subjects, adipose tissue LPL decreases during fasting [3,4] and increases with carbohydrate feeding [5][6][7].…”
mentioning
confidence: 99%
“…
Lipoprotein lipase plays a key role in the catabolism of triglyceride(TG)-rich lipoproteins [1], and it is generally accepted that the activity of this enzyme is decreased in insulin-deficient states [2][3][4]. While alterations in LPL have long been suspected in insulin resistance [1,5], the situation concerning the relationship between LPL and insulin-mediated glucose disposal is more complicated.
…”
mentioning
confidence: 99%